Central Bank Losses and Experiences in Selected Countries - Dziobek, Claudia (IMF Working Papers; Working Paper ;, 2005)
Under normal circumstances, a central bank should be able to operate at a profit with a core level of earnings derived from seigniorage. Losses have, however, arisen in several central banks from a range of activities including monetary operations under extreme conditions and financial sector restructuring. The paper discusses the impact of losses on central bank operations and lays out the principles and practices for handling central bank losses. It is suggested that losses should be disclosed as a reduction of the central bank's net worth unless covered by the government. Governments may cover losses through recapitalization of the central bank, and this will create a new central bank asset, usually in the form of government securities held by the central bank. Six case studies illustrate the circumstances under which losses may arise, their coverage, and central banks' disclosure practices.